2012
DOI: 10.1039/c2mb25151e
|View full text |Cite
|
Sign up to set email alerts
|

Large scale phosphoproteome analysis of LNCaP human prostate cancer cells

Abstract: Prostate cancer is the most frequently diagnosed cancer among men in the western world. The androgen receptor, a phosphoprotein, is suspected to be involved in all stages of the prostate cancer. Androgen receptor activity can be modulated by various kinases such as PKA, MAPK, AKT, and Src. Phosphorylation is an important post-translational modification and serves as a molecular on/off switch to regulate signaling. Disruptions of cellular phosphorylation are associated with various diseases such as cancer and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 78 publications
(128 reference statements)
0
10
0
Order By: Relevance
“…Subsequent phospho-proteome analyses of HeLa (Beausoleil et al, 2004), lymphoma (Shu et al, 2004), and prostate cancer cells (Myung and Sadar, 2012) confirm the prevalence of SF1 SPSP phosphorylation and suggest a role in cancer initiation or progression. A kinase called Kinase Interacting with Stathmin (KIS), or UHMK1, specifically phosphorylates SF1 serines at position 80 and 82 within the SPSP motif (Manceau et al, 2008; Manceau et al, 2006).…”
Section: Introductionmentioning
confidence: 81%
“…Subsequent phospho-proteome analyses of HeLa (Beausoleil et al, 2004), lymphoma (Shu et al, 2004), and prostate cancer cells (Myung and Sadar, 2012) confirm the prevalence of SF1 SPSP phosphorylation and suggest a role in cancer initiation or progression. A kinase called Kinase Interacting with Stathmin (KIS), or UHMK1, specifically phosphorylates SF1 serines at position 80 and 82 within the SPSP motif (Manceau et al, 2008; Manceau et al, 2006).…”
Section: Introductionmentioning
confidence: 81%
“…Taken together, all these reports highlight the importance of the cell-ECM interactions for studying transcriptomes and proteomes from both normal and tumoral cells, at in vitro systems [3][4][5][8][9][10]13,[16][17][18]. In this sense, future investigators should be aware that RWPE-1, LNCaP and PC-3 cells, and most likely other tumor cells, require cell-ECM interaction in order to express detectable levels of MMPs on their CM.…”
Section: Discussionmentioning
confidence: 99%
“…Castration-resistant prostate cancer (CRPC) is the most advanced form of prostate cancer exhibiting reduced survival, with reported values varying between 9 and 30 months [2]. In this sense, in vitro culture systems are widely employed in prostate cancer research and, more recently, for transcriptome and proteomic analysis because the cultures reproduce rapidly and readily [3]. Although these monolayer cultures provide rapid and important results, they recreate only a fraction of a complex scenario [4].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies using the parental LNCaP PrCa cell line identified phosphopeptides corresponding to several actionable kinase targets. These included BRAF, PIK3C2G, STK39, CDK1, MAPK2, AKT1, PRKD1, casein kinase 1 and 2 (CK2A1, CK2A2), and glycogen synthase kinase 3 (GSK3B) ( 58 60 ).…”
Section: Phosphoproteomics In Prcamentioning
confidence: 99%